Corporate Social Responsibility and Latin American business fabric: philosophy of transparency or marketing tool? - Da Costa Pimenta, Clayson Cosme (2022)
This research explores the panorama of Corporate Social Responsibility (CSR) in Latin America and the Caribbean from a critical perspective. The main objective of the work is to check whether CSR is a new business philosophy based on transparency or, on the contrary, a marketing tool. The hypothesis of the article is that, although there are a number of companies that have sincerely adopted CSR, a growing number of companies have formally adopted the discourse of CSR as a marketing tool, to attract new customers or to retain customers. From the methodological point of view, the work uses systematic bibliographic review and critical analysis of specialized literature and published in scientific journals. The results of the study confirm that Latin American companies increasingly assume with greater sincerity the policies and philosophy of CSR, although it is concluded that sometimes it is difficult to measure the degree of honesty and authenticity of the assumption of the principles of CSR.